Optimal dietary linoleic acid to linolenic acid ratio improved fatty acid profile of the juvenile tambaqui (Colossoma macropomum) - Paulino, Renan Rosa; Pereira, Raquel Tatiane; Fontes, Tafanie Valacio; Oliva-Teles, Aires; Peres, Helena; Carneiro, Dalton Jose [UNESP]; Rosa, Priscila Vieira (Elsevier B.V., 2018)
The present study aimed to evaluate the effect of dietary linoleic acid to linolenic acid (LNA/ALA) ratio on growth performance, feed utilization, plasma metabolite profiles, and muscle and liver fatty acid profiles of juvenile tambaqui Colossoma macropomum. Six diets were formulated to contain incremental levels of corn oil (rich in LNA) from 0 to 7% at the expense of linseed oil (rich in ALA), resulting in dietary LNA/ALA ratios ranging from 3.1 to 26.9. A control diet including fish oil was also formulated. The trial lasted 49 days, and each diet was assigned to six groups of fish with an initial body weight of 43 g. At the end of the trial, dietary LNA/ALA ratio did not affect growth performance, feed utilization, and plasma metabolites profile, except for HDL that was lower in fish fed the 3.8 LNA/ALA diet than the 3.1 or 5.0 LNA/ALA diets. Whole-body protein content was lower in fish fed the control and 3.1 LNA/ALA diets. Composition of triglycerides, glucose and protein of liver and muscle was unaffected by dietary treatments. Eicosapentaeneoic acid (EPA, 20: 5n-3) plus docosahexaenoic acid, (DHA, 22: 6n-3) content of muscle decreased with the increase of LNA/ALA ratio. Fish fed 3.9-5.6 LNA/ALA diet showed the highest concentration of muscle ARA (arachidonic acid, 20: 4n-6) and EPA+ DHA among vegetable oil diets, though lower than that of fish fed the fish oil based diet. In conclusion, dietary LNA/ALA ratio should range between 3.9-5.6 to produce fillets with high EPA, DHA, and ARA contents, thus improving the nutritional quality of tambaqui fillets for human consumers.
Keywords: Lipid nutrition; Essential fatty acids; Neotropical fish; EPA; DHA; ARA